(untitled) - Lazar, Gillian (Cambridge, New York, 1993)
The book explores different approaches to using literature with learners at all levels; suggests criteria for selecting and evaluating materials for classroom use; identifies some of the distinctive features of novels, short stories, poems and plays so that these can be successfully exploited in the classroom; provides a wide range of practical ideas and activities for developing materials which teachers can use with their own learners; encourages the observation and assessnebt of lessons which use literary texts
Keywords: Literature; Study and teaching (elementary)